2023
DOI: 10.3390/vetsci10010061
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Laparoscopic Access in Standing Horses Using Cannula and Trocar Units Developed for Human Medicine

Abstract: First cannulation is a critical manoeuvre in equine laparoscopy. This retrospective study aimed at the comparison of the frequency and type of complications detected when using different human laparoscopy devices for laparoscopic access in standing horses, and the influence of body condition in such complications. Forty-four procedures were included, and retrieved data comprised cannula insertion technique, body condition, and type and frequency of complications. Laparoscopic access techniques were classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…This approach has been clinically demonstrated to provide convenient and rapid port insertion while exhibiting a decreased incidence of complications compared to other procedures. 19 Six studies [28][29][30] have demonstrated that it is possible to perform LPS with minimal pneumoperitoneum pressure. None of the studies, however, evaluated the effects on recovery quality.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been clinically demonstrated to provide convenient and rapid port insertion while exhibiting a decreased incidence of complications compared to other procedures. 19 Six studies [28][29][30] have demonstrated that it is possible to perform LPS with minimal pneumoperitoneum pressure. None of the studies, however, evaluated the effects on recovery quality.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that it is an important prototype; although this study is preliminary, this device can be improved and adapted to single-site laparoendoscopic (or LESS) approaches. Advances related to cryptorchidectomy in standing horses depend on improvements and discoveries using equipment such as this [1,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The new device evaluated in live animals proved to be efficient for cryptorchidectomy of testicles retained in the inguinal region in cases not complicated by adhesions [6,9]. Laparoscopy with a new device allowed a broad intra-abdominal inspection and tissue manipulation in the inguinal region of standing horses, a place where cryptorchid testicles are commonly retained, allowing easy identification of the gonadal and an immediate diagnosis of these testicles [1,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations